Startup projects machine translation strategy in examples and problems - Bukhkalo, Svetlana Ivanovna; Ageicheva, Anna Oleksandrivna; Vypovska, Anastasiia Yevheniivna; Derkunska, Zhanna Viktorivna; Pshychkina, Nataliia Georgievna (Національний технічний університет "Харківський політехнічний інститут", 2021)
The importance of ICT usage implementation in the startup project machine translation is analyzed. It has been studied that translation is of great importance for any startup project for establishing relationships with potential clients around the world. The role of the translator in the startup project is studied. Translation has been proved to be important for any startup project to build relationships with potential clients around the world. A comprehensive analysis of the translation of startup projects from Ukrainian into English using the latest information and communication technologies in this process. Peculiarities of using modern ICT in translating the description of startup projects from Ukrainian into English are obvious. Exploring the use of information and computer technology in the translation process. It is determined that it is important for a translator of a startup project to understand all the features of using the software, choose the appropriate programs or online tools and develop a strategy for the translation process in the project. The results of this work are very important and necessary for further study of the features of the use of ICT in the translation of startup projects. Startup projects machine translation strategy is given in examples and problems for better understanding.

Проаналізовано важливість впровадження ІКТ у стартап проекті з машинним перекладом. Доведено, що переклад має велике значення для будь-якого стартап-проекту для налагодження стосунків з потенційними клієнтами по всьому світу. Досліджена роль перекладача в стартап-проєкті. Доведено, що переклад є важливим для будь-якого стартап проекту для налагодження відносин з потенційними клієнтами по всьому світу. Виконано комплексний аналіз перекладу стартап проєктів з української мови на англійську із застосуванням новітніх інформаційно-комунікаційних технологій у цьому процесі. Виявлено особливості використання сучасних ІКТ при перекладі опису стартап проєктів з української мови на англійську. Дослідженню використання інформаційних та комп’ютерних технологій у процесі перекладу. Визначено, що перекладачу стартап проекту важливо розуміти всі особливості використання програмного забезпечення, вибрати належні програми чи онлайн-інструменти та розробити стратегію перекладацького процесу. Результати даної роботи є дуже важливими та необхідними для подальшого дослідження особливостей використання ІКТ у перекладі стартап-проєктів.
Стратегія машинного перекладу стартап проєктів в прикладах і задачах
Keywords: ICT; Information and Communications Technology; ІКТ; Інформаційно-комунікаційні технології